OPEC: Future Challenges - Khadduri, W (Oxford Institute for Energy Studies, 2011)
OPEC is undergoing a belated honeymoon period on its fiftieth anniversary. This is reflected in the success of maintaining a high price range ($75–85 per barrel), or even higher, as well as the professional management of the Organization, in contrast to the previous periods of flagrant disrespect of production policies and quotas. Basically, there exists today a clear understanding and unanimous agreement among the member states, despite political differences among them, to implement the main objective of the Organization – the achievement of a reasonable and just return for the export of hydrocarbons.